Power measurement in cycling using inductive coupling of energy and data - Tielert, R.; Wehn, N.; Jaitner, T.; Volk, R. (The Engineering of sport 7, Volume 1, 2008)
The power exerted on the pedal is the most reliable parameter to determine the training load in cycling biomechanically and hence a crucial factor to optimize performance. Commercial power meters are meanwhile part of the Standard equipment of professional cyclists, but also used by an increasing number of non professional cyclists. In this paper we present a System to measure the torque, the cadence and power in cycling using inductive coupling of energy and data. Sensors and signal pre-processing electronics work without any battery on the turning parts. Under dynamic conditions, an overall accuracy of ±10% can be determined. The newly developed power meter can be characterized by low maintenance and energy consumption as well as by an increased number of detected physical values (e.g. 30 degree sectors, individual measurements of left and right pedals). This allows long-term measures as well as more detailed analyses of the pedalling techniques (coordination between left and right leg, e.g.). The first prototype has been successfully integrated into a bicycle and was tested under conditions of training. A second prototype that allows more detailed measures (e.g. section-wise detection of torque and power) runs under laboratory settings.